(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To evaluate the effectiveness and safety of polypropylene mesh in the surgical reconstruction of pelvic floor in patients with pelvic organ prolapse (POP) at Nghe An Friendship General Hospital. Subjects and Methods: Case reports of female patients with pelvic organ prolapse treated at Nghe An General Friendship Hospital who assigned for surgery to reconstruct the pelvic floor with polymeric mesh. Results: Between June 2020 to June 2021, among 48 selected patients underwent surgery, the average age was 61.3 years, the proportion of patients who were in pregnant equal to or greater than 3 times was 83.3%; The proportion of bladder prolapse, uterine prolapse and rectus prolapse were 89.5%, 83.3% and 31.2%, respectively. Laparoscopic surgery accounted for 72.8% of total cases and sacrocolpopexy accounted for 28.2%. The average time of sacrocolpopexy was 130 ± 39 minutes with the blood loss of 160±37 ml. The average time of mesh placement for reconstruction of the anterior wall of the vagina was 61±6 minutes, the average blood loss was 56 ± 13 ml. Sacral pain occurred in 3 out of 48 patients. Overactive bladder was seen in 3 out of 48 patients. Conclusions: The placement of polymeric mesh to repair the pelvic organ prolapse can be perfomed transvaginal or laparoscopy surgery. In our study, there was no recurrence during follow-up. The rate of early and long term complications was low. The quality of life of patients was improved after surgery.